The evolution of green spaces within institutional plots in Yeka Sub-City, Addis Ababa, Ethiopia - Utant Debebe; Utant Debebe; Alazar Assefa (Frontiers in Sustainable Cities)
Understanding the dynamics of urban green coverage is crucial for informing urban planning and design decisions that foster sustainable cities. This study employed Google Earth imagery and Exploratory Spatial Data Analysis (ESDA) to investigate the changes in urban green coverage within institutional plots in Yeka Sub-City, Addis Ababa, over a twenty-year period from 2003 to 2023. Subsequent image processing and analyses were conducted using GIS and ERDAS Imagine software. The findings revealed a gradual decline in green space coverage by 10.86 hectare, primarily attributed to the expansion of built-up areas and an increase in bare land. These changes suggest that the trend is driven by institutions constructing new facilities and optimizing land use within their compounds. The moderate positive spatial autocorrelation (Moran’s I value of 0.60) indicated that changes in green space were not randomly distributed but tended to cluster in specific areas. This study emphasizes the importance of preserving and enhancing existing green spaces within institutional compounds to promote environmental, social, and economic sustainability. By integrating green space preservation into urban planning and institutional land management practices, policymakers can ensure balanced urban development that aligns with environmental sustainability goals.